Regulation of X-Ray Irradiation on the Activity and Expression Levels of CYP1A2 and CYP2E1 in Rats - Li, Xiang-Yang; Qu, Ning; Wang, Xue-Jun; Yang, Jian-Xin; Xin, Yuan-Yao; Zhu, Jun-Bo; Bai, Xue; Duan, Ya-Bin (Frontiers in Pharmacology, 2020)
The objective of this study was to investigate the regulation of X-ray irradiation on the activity and protein and mRNA expression levels of CYP1A2 and CYP2E1 in rats. Rats were randomly divided into 0 Gy (control), 1 Gy (low dose irradiation), and 5 Gy (high-dose irradiation) groups. CYP1A2 and CYP2E1 activity was evaluated from changes in pharmacokinetic parameters of caffeine and chlorzoxazone, respectively. The plasma concentrations of the probe drugs were determined by high-performance liquid chromatography (HPLC). Enzyme-linked immunosorbent assay (ELISA) and real-time polymerase chain reaction (PCR) tests were used to analyze the protein and mRNA expression levels of CYP1A2 and CYP2E1, respectively. The AUC0-12 of caffeine was decreased by 1.7- and 2.5-fold, and the CL was increased by 1.8- and 2.6-fold in the 1 Gy and 5 Gy groups, respectively, compared to the 0 Gy group. The AUC0-10 of chlorzoxazone was 1.4- and 1.8-fold lower, and the CL was 1.4- and 1.9-fold higher in the 1 Gy and 5 Gy groups, respectively, compared to the 0 Gy group. The metabolism of caffeine and chlorzoxazone decreased under X-ray irradiation as CL levels increased and AUC levels decreased, suggesting that CYP1A2 and CYP2E1 activity is enhanced in rats after X-ray irradiation. Compared to that of the 0 Gy group, the protein expression level of CYP1A2 was measured as 28.3% and 38.9% higher in the 1 Gy and 5 Gy groups, respectively. The protein expression level of CYP2E1 was 48.4% higher in the 5 Gy group compared to the 0 Gy group, and there was no statistically significant difference between 0 Gy and 1 Gy. Compared to the 0 Gy group, the mRNA expression level of CYP1A2 was 200% and 856.3% higher in the 1 Gy and 5 Gy group, respectively, whereas the mRNA expression level of CYP2E1 was 89.0% and 192.3% higher in the 1 Gy and 5 Gy groups, respectively. This study reveals significant changes in the activity and protein and mRNA expression levels of CYP1A2 and CYP2E1 in rats after exposure to X-ray irradiation.